2018
DOI: 10.1007/s11207-018-1328-z
|View full text |Cite
|
Sign up to set email alerts
|

A Curious History of Sunspot Penumbrae: An Update

Abstract: The ratio of penumbral to umbral area of sunspots is an important topic for solar and geophysical studies. Hathaway (Solar Physics, 286, 347, 2013) found a curious behaviour in this parameter for small sunspot groups (areas smaller than 100 millionths of solar hemisphere, msh) using records from Royal Greenwich Observatory (RGO). Hathaway showed that penumbra-umbra ratio decreased smoothly from more than 7 in 1905 to lower than 3 by 1930 and then increased to almost 8 in 1961. Thus, Hathaway proposed the exis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…The opposite trends of the two diagrams is conspicuous, larger umbrae decay faster than smaller ones and their areas with respect to their penumbrae are smaller than in small sunspots. This is in agreement with the theoretical result of Rempel & Cheung (2014) that the larger penumbra stabilizes the sunspot; but it contradicts to the results of Brandt et al (1990) and Carrasco et al (2018b) and Hathaway (2013). This dependence is also in contrast to Hoyt & Schatten (1997), who found a linear relationship between the U/P values and the decay rates.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The opposite trends of the two diagrams is conspicuous, larger umbrae decay faster than smaller ones and their areas with respect to their penumbrae are smaller than in small sunspots. This is in agreement with the theoretical result of Rempel & Cheung (2014) that the larger penumbra stabilizes the sunspot; but it contradicts to the results of Brandt et al (1990) and Carrasco et al (2018b) and Hathaway (2013). This dependence is also in contrast to Hoyt & Schatten (1997), who found a linear relationship between the U/P values and the decay rates.…”
Section: Resultssupporting
confidence: 59%
“…Brandt et al (1990) studied 126 sunspots observed around 1980 and pointed out the U/P value is 0.24 for small and 0.32 for large spots. Carrasco et al (2018b) found different behavior in the variation of U/P ratio of the small and large groups by using the Royal Greenwich Observatory (RGO) series. The larger groups do not show significant changes from year to year while the smaller groups do.…”
Section: Introductionmentioning
confidence: 99%
“…Hathaway (2013) showed that the ratio values decreased smoothly from 7 in 1905 to lower than 3 around 1930 and then smoothly increased to 7 until 1961. However, the secular variation in the penumbra-umbra ratio for small sunspot groups was not confirmed by Carrasco et al (2018) using the Coimbra sunspot catalogue.…”
Section: Introductionmentioning
confidence: 84%
“…Known examples of long series are those of the Royal Greenwich Observatory, UK (Willis et al, 2013), Paris Observatory, Meudon, France (Mein and Ribes, 1990), Kodaikanal, India (Mandal et al, 2017), Mount Wilson, USA (Lefebvre et al, 2005), Debrecen, Hungary (Baranyi, Győri, and Ludmány, 2016) and Arcetri, Italy (Ermolli et al, 2009). Other programs were also implemented in Ebro and San Fernando in Spain Curto et al, 2016) and Coimbra, Portugal (Mouradian and Garcia, 2007;, 2011Carrasco et al, 2018a and2018b). The Coimbra Astronomical Observatory (currently Geophysical and Astronomical Observatory of the University of Coimbra, "Observatório Geofísico e Astronómico da Universidade de Coimbra", hereafter OGAUC) started in 1925 a solar observation program that continues today, with essentially the same acquisition system, leading to a large and consistent database.…”
mentioning
confidence: 99%
“…The urgent need for historical astronomical data digitization and preservation enabling scientific research is referred by Pevtsov et al (2019). Carrasco et al (2018a) provided a machine-readable version of sunspot data recorded in the Coimbra historical solar catalogues. Data on other solar features have not yet been addressed.…”
mentioning
confidence: 99%